Manželské etudy po 20 letech: Zuzana a Stanislav - Třeštíková, Helena (Czech Republic : Beckov, Anna, 2006)
During the period 1981–2005, filmmaker Helena Třeštíková followed the progress of couples who married at the beginning of the 1980s and, over the subsequent two decades, had to confront their dreams and ideals with a society in transformation. “You and I, that’s who we are…” such were the lyrics of Zuzana’s and Stanislav’s favourite band Olympic; however, they never managed to accomplish the “we.” They married out of necessity; she was still in her final year at grammar school, he was an electrical technician just one year older. Due to difficult housing conditions, they started living together only three years after their wedding. Though they already had two children at the time, the immaturity of their early marriage as well as their completely different characters soon started to take their toll. While energetic Stanislav kept moving forward in life, towards new interests, a new job and a new relationship, ambitionless Zuzana, whom motherhood prevented from making her own way in life, remains passive and is having difficulties finding a new partner.
Verzio Film Festival Submission
Verzio Film Festival Submission